Quality assessment program for EuroFlow protocols: summary results of four-year (2010-2013) quality assurance rounds - Kalina, Tomas; Flores-Montero, Juan; Lecrevisse, Quentin; Pedreira, Carlos E; van der Velden, Vincent H J; Novakova, Michaela; Mejstrikova, Ester; Hrusak, Ondrej; Böttcher, Sebastian; Karsch, Dennis; Sędek, Łukasz; Trinquand, Amelie; et al. (Cytometry. Part A, 2015)
Flow cytometric immunophenotyping has become essential for accurate diagnosis, classification, and disease monitoring in hemato-oncology. The EuroFlow Consortium has established a fully standardized "all-in-one" pipeline consisting of standardized instrument settings, reagent panels, and sample preparation protocols and software for data analysis and disease classification. For its reproducible implementation, parallel development of a quality assurance (QA) program was required. Here, we report on the results of four consecutive annual rounds of the novel external QA EuroFlow program. The novel QA scheme aimed at monitoring the whole flow cytometric analysis process (cytometer setting, sample preparation, acquisition and analysis) by reading the median fluorescence intensities (MedFI) of defined lymphocytes' subsets. Each QA participant applied the predefined reagents' panel on blood cells of local healthy donors. A uniform gating strategy was applied to define lymphocyte subsets and to read MedFI values per marker. The MedFI values were compared with reference data and deviations from reference values were quantified using performance score metrics. In four annual QA rounds, we analyzed 123 blood samples from local healthy donors on 14 different instruments in 11 laboratories from nine European countries. The immunophenotype of defined cellular subsets appeared sufficiently standardized to permit unified (software) data analysis. The coefficient of variation of MedFI for 7 of 11 markers performed repeatedly below 30%, average MedFI in each QA round ranged from 86 to 125% from overall median. Calculation of performance scores was instrumental to pinpoint standardization failures and their causes. Overall, the new EuroFlow QA system for the first time allowed to quantify the technical variation that is introduced in the measurement of fluorescence intensities in a multicentric setting over an extended period of time. EuroFlow QA is a proficiency test specific for laboratories that use standardized EuroFlow protocols. It may be used to complement, but not replace, established proficiency tests. © 2014 International Society for Advancement of Cytometry.
Keywords: lymfom; referenční hodnoty; EuroFlow; leukemie; Healthy Volunteers; referenční standardy; řízení kvality; lymphoma; podskupiny lymfocytů; imunofenotypizace; Lymphoma; quality assessment; Europe; immunophenotyping; Reference Standards; leukemia; Immunophenotyping; Lymphocyte Subsets; Quality Control; Flow Cytometry; flow cytometry; Reference Values; průtoková cytometrie; Leukemia; zdraví dobrovolníci pro lékařské studie; Evropa